Interaction between 1-pyrenesulfonic acid and albumin: Moving inside the protein - Bertozo, Luiza de Carvalho [UNESP]; Philot, Eric Allison; Lima, Angélica Nakagawa; de Resende Lara, Pedro Túlio; Scott, Ana Lígia; Ximenes, Valdecir Farias [UNESP] (Elsevier, 2019)
Due to the high sensitivity to alterations in microenvironment polarity of macromolecules, pyrene and its derivatives have long been applied in biosciences. Human serum albumin (HSA), besides its numerous physiological functions, is the main responsible by transport of endogenous and exogenous compounds in the circulatory system. Here, a comprehensive study was carry out to understand the interaction between HSA and the pyrene derivative 1-pyrenesulfonic acid (PMS), which showed a singular behaviour when bound to this protein. The complexation of PMS with HSA was studied by steady state, time-resolved and anisotropy fluorescence, induction of circular dichroism (ICD) and molecular docking. The fluorescence quenching of PMS by HSA was abnormal, being stronger at lower concentration of the quencher. Similar behaviour was obtained by measuring the ICD signal and fluorescence lifetime of PMS complexed in HSA. The displacement of PMS by site-specific drugs showed that this probe occupied both sites, but with higher affinity for site II. The movement of PMS between these main binding sites was responsible by the abnormal effect. Using the holo (PDB: ID 1A06) and apo (PDB: ID 1E7A) HSA structures, the experimental results were corroborated by molecular docking simulation. The abnormal spectroscopic behaviour of PMS is related to its binding in different regions in the protein. The movement of PMS into the protein can be traced by alteration in the spectroscopic signals. These findings bring a new point of view about the use of fluorescence quenching to characterize the interaction between albumin and ligands.
Keywords: 1-pyrenesulfonic acid; Albumin; Fluorescence anisotropy; Fluorescence quenching; Induced circular dichroism; Molecular docking